Wednesday

April 16, 2014

April 16, 2014

Posted by **Lindsay** on Monday, July 16, 2012 at 12:42am.

2. ((cos(x)cot(x))/(1 - sin(x)))-1

- Trigonometry -
**Shen**, Monday, July 16, 2012 at 4:01am1) (cos^2x+1+2sinx+sin^2x)/cosx(1+sinx)

= 2+2sinx/cosx(1+sinx)

= 2(1+sinx)/cosx(1+sinx)

= 2/cosx

= 2secx

i'm going to assume you know the identities i.e. cos^2x+sin^2x=1

2) (cosx x cosx/sinx)/-sinx

= cos^2x/sinx/sin^2x

= cos^2x/-sin^2x

= -cot^2x

**Related Questions**

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Trigonometry - Prove the following trigonometric identities. please give a ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

maths - trigonometry - I've asked about this same question before, and someone ...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

trigonometry - how do i simplify (secx - cosx) / sinx? i tried splitting the ...

Trigonometry - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/...